Examining the Effect of Different Solvents on Fatty acid Profile and Nutritional Properties of Oil Extracted from TWO Wild almond Species of Amygdalus Scoparia and Amygdalus Lycioides - Amir Peikar ,Rezvan Mousavi Nadoushan, Mohammad Rabbani, Farzad Karimpour (International Journal of Modern Agriculture, 2021)
In the present study, we examined the effect of changing different solvents in the process of extracting oil from two species of wild almond: Amygdalus Lycioides (A.Ly) and Amygdalus Scoparia (A.Sc). The effect of these changes on the profile of fatty acids and their nutritional value was further investigated. These almonds were collected from some regions of Kohgiluyeh Province, Iran. The level of total unsaturated fatty acids (TUFA) in the extracted oils was more than 89%, which included oleic acid and linoleic acid. The highest level of unsaturated fatty acids belonged to palmitic acid and stearic acid. In the present study, three types of solvents, including hexane, diethyl ether, and petroleum ether, were used in the process of oil extraction from almond kernels. The effect of these solvents alone and the interaction effect on the extraction process of fatty acid profiles were examined. The nutritional quality indices such as atherogenic (AI), thrombogenic (TI), and hypocholesterolemic:hypercholesterolemic FA ratio (HH) were also calculated in differtent solvent extraction procedures. The process of extracting oil from almond A.Ly with the help of petroleum ether (100%) solvent showed the lowest amount of AI (0.05) and TI (0.15). In this regard, the highest amount of HH (17.32) was observed in the same extraction process. In the present study, the best solvent for the extraction of saturated and unsaturated fatty acids was identified and the iodine value was determined for each process. Selecting a suitable solvent for the selective extraction of saturated and unsaturated fatty acids and specifying indices for assessing the nutritional value of oils may be conducive to producing high-quality almond oil in the future.